What is the link between regret and weakness of will?. (2nd April 2016) - Doucet, Mathieu
Abstract: This paper argues (a) that most contemporary accounts of weakness of will either implicitly or explicitly assume that regret is a typical or even necessary element of standard cases of weakness of will and (b) that this assumption is mistaken. I draw on empirical and philosophical work on self-assessment to show that regret need not accompany typical weak-willed behavior, and that we should therefore revise the dominant account of the difference between weakness of will and (mere) changes of mind.